Czech Brain Aging Study (CBAS): prospective multicentre cohort study on risk and protective factors for dementia in the Czech Republic - Ross Andel; Katerina Sheardova; Martin Vyhnalek; Zuzana Nedelska; Jan Laczo; Rafal Marciniak; Jiri Cerman; Ondrej Lerch; Jakub Hort (BMJ Open)
Purpose Identification of demographic, physical/physiological, lifestyle and genetic factors contributing to the onset of dementia, specifically Alzheimer disease (AD), and implementation of novel methods for early diagnosis are important to alleviate prevalence of dementia globally. The Czech Brain Aging Study (CBAS) is the first large, prospective study to address these issues in Central/Eastern Europe by enrolling non-demented adults aged 55+ years, collecting a variety of personal and biological measures and tracking cognitive function over time.Participants The CBAS recruitment was initiated in 2011 from memory clinics at Brno and Prague University Hospitals, and by the end of 2018, the study included 1228 participants. Annual follow-ups include collection of socioeconomic, lifestyle and personal history information, neurology, neuropsychology, laboratory, vital sign and brain MRI data. In a subset, biomarker assessment (cerebrospinal fluid (CSF) and amyloid positron emission tomography) and spatial navigation were performed. Participants were 69.7±8.1 years old and had 14.6±3.3 years of education at baseline, and 59% were women. By the end of 2018, 31% finished three and more years of follow-up; 9% converted to dementia. Apolipoprotein E status is available from 95% of the participants. The biological sample bank linked to CBAS database contained CSF, serum and DNA.Findings to date Overall, the findings, mainly from cross-sectional analyses, indicate that spatial navigation is a promising marker of early AD and that it can be distinguished from other cognitive functions. Specificity of several standard memory tests for early AD pathology was assessed with implications for clinical practice. The relationship of various lifestyle factors to cognition and brain atrophy was reported.Future plans Recruitment is ongoing with secured funding. Longitudinal data analyses are currently being conducted. Proposals for collaboration on specific data from the database or biospecimen, as well as collaborations with similar cohort studies to increase sample size, are welcome. Study details are available online (www.cbas.cz).